Intestinal Ultrasound to Assess Disease Activity in Ulcerative Colitis: Development of a novel UC-Ultrasound Index. (7th January 2021) - Bots, Steven; Nylund, Kim; Löwenberg, Mark; Gecse, Krisztina; D'Haens, Geert
Abstract: Introduction: Intestinal ultrasound [IUS] is useful to assess inflammation in ulcerative colitis [UC] patients. We aimed to develop an ultrasonographic activity index using endoscopy as the reference standard. Methods: Patients were included consecutively. IUS was performed within 3 weeks from endoscopy. IUS parameters and endoscopy were compared for each colonic segment [except the rectum]. The best parameters were used to construct a UC-IUS index, which was correlated with endoscopic disease activity using the Spearman's rank test. Results: In 60 patients, 207 colonic segments were evaluated endoscopically. Bowel wall thickness [BWT] > 2.1 mm was optimal to discriminate between Mayo 0 and Mayo 1–3 (sensitivity 82.6%; specificity 93.0%; area under the curve [AUC] 0.910), a cut-off of 3.2 mm was optimal to discriminate between Mayo 0–1 and Mayo 2–3 [sensitivity 89.1%; specificity 92.3%; AUC 0.946] and BWT > 3.9 mm was optimal for detection of Mayo 3 [sensitivity 80.6%; specificity 84.1%; AUC 0.909]. The presence of colour Doppler signal [CDS] predicted active disease, stretches of CDS were associated with Mayo 2–3, lack of haustrations predicted active disease and fat wrapping was associated with severe disease. Inter- and intra-rater intraclass correlation for BWT was substantial. Inter-rater agreement for CDS was substantial and ranged from slight to substantial for haustrations. Intra-rater agreement for CDS was substantial and ranged from moderate to almost perfect for haustrations. The index showed strong correlation with endoscopic disease activity [Mayo: ρ 0.830; p < 0.001, UCEIS: ρ 0.759; p < 0.001]. Conclusion: We developed an UC-IUS index which showed strong correlation with endoscopic disease activity using internal validation. It is currently being validated in prospective studies.